(untitled) (Research, Society and Development, 2019)
The present work aimed to raise, through a literature review, the main economic points triggered by the phenomenon of truck drivers’ manifestations on federal and state highways in Brazil. To the general apparatus, it is objectified by the fragmentation of the political and economic information about the diesel crisis. Therefore, it was intended to synthesize the data of the most relevant losses that express with greater clarity the result of the most expressive social movement in the first half of 2017 through a research of a descriptive nature. The objective is to understand the impact generated by the economic downturn in Brazil, as well as the possibility of creating a parameter to socioeconomic dimensions triggered by phenomena of this nature, with losses ranging from R 75 billion to R 100 billion.